THE INFLUENCE OF FUNCTIONAL AND COGNITIVE ATTRACTIVENESS TOWARD THE INITIATION OF TRANSPORT STOP IN SUMATRA HIGHWAY - Iswi, Aulia
Development Axes Theory states that the transportation network is built to communicate or joining two or more Growth Pole (end point) directly. The existence of development axes will generate other activities around the mid-point of the axes which will expand along the development axes linearly. However, in this Development Axes Theory, it has not been explained how the flow of goods and people along the axes will generate an activity to grow as a transport-stop. Some study suggests that there is an attractiveness between the flow of transportation and the development of transport-stop. The influence of attractiveness toward the development of transport-stop, will occur if there is an economic impact toward the surrounding area. The economic impact in this study is narrowed to the expansion of the economic activities and the absorption of local labor affected by transportstop. In this study, focus on the influence of functional and cognitive attractiveness toward the initiation of transport-stop based on trade and service activity. By comparing the two location of transport-stop with a different economic impact, the attractiveness between the transport-stop will be examined. Development axes under this study is Sumatra Highway. Empirically, Rumah Makan Siang Malam as a transport-stop affect the growth of the surrounding area by creating a new economic activity as well as the absorption of local labor, while Rumah Makan Bukit Kahuripan can not influence the activity around it. From these differences, presumed that there is attractiveness which influence the growth of the two transport-stop. The influence of attractiveness will be an initial impulse of the growth of transport-stop. This study has quantitative approach as measured by 1) the differences of transport-stop growth with Lieberson’s Similarity Measure and location attraction index; 2) identify the attractiveness toward the traveler in Sumatra Highway with descriptive quantitative analysis from revealed preference questioner; and 3) identify the attractiveness toward the growth differences between the two transport-stop with discriminant analysis. The result shows that the growth differences between the two transport-stop influenced by 1) additional activities; 2) amenities; 3) diversity of land use; 4) surrounding environment of transport-stop; 5) food quality; 6) the needs of traveler to be on time; 7) spacious restaurant; 8) the fear of traveler to travel at night; and 9) the existence of traveler using tour and travel. These attractions later become the initial impulse of the transport-stop growth as explained in the Development Axes Theory, flow of goods and people along the axes will generate an activity to grow as a transport-stop.